2014
DOI: 10.1038/nsmb.2919
|View full text |Cite
|
Sign up to set email alerts
|

Local slowdown of translation by nonoptimal codons promotes nascent-chain recognition by SRP in vivo

Abstract: The genetic code allows most amino acids a choice of optimal and nonoptimal codons. We report that synonymous codon choice is tuned to promote interaction of nascent polypeptides with the signal recognition particle (SRP), which assists in protein translocation across membranes. Cotranslational recognition by the SRP in vivo is enhanced when mRNAs contain nonoptimal codon clusters 35–40 codons downstream of the SRP-binding site, the distance that spans the ribosomal polypeptide exit tunnel. A local translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
199
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(210 citation statements)
references
References 57 publications
9
199
2
Order By: Relevance
“…Recent analyses of ribosome profiling data have revealed mRNA-programmed ribosome pauses that enhance SRP binding and faithful membrane integration (39,40). In yeast, these events are mediated by rare codons, whereas in Escherichia coli they are mediated by ORF-internal Shine-Dalgarno elements.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses of ribosome profiling data have revealed mRNA-programmed ribosome pauses that enhance SRP binding and faithful membrane integration (39,40). In yeast, these events are mediated by rare codons, whereas in Escherichia coli they are mediated by ORF-internal Shine-Dalgarno elements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this impairment is a striking example in which preceding translational pausing is necessary for the recognition of the ER-targeting signal by SRP. Similarly, Frydman and coworkers (35) recently reported that SRP preferentially recognizes a set of proteins harboring a signal sequence with a downstream cluster of suboptimal codons, which slows translational elongation. Further, Weissman and coworkers (36) showed that artificial translational arrest by cycloheximide treatment enables the ER localization of a subset of cytosolic mRNAs encoding the proteins harboring a first transmembrane segment or a signal sequence in the C-terminal region (from 50 to 150 codons before the termination codons).…”
Section: Discussionmentioning
confidence: 99%
“…The coimmunoprecipitated proteins were eluted by incubation in 2× sample buffer [125 mM Tris·HCl (pH 6.8), 4% SDS, and 15% sucrose] containing 50 mM DTT and analyzed by Western blotting. For immunoprecipitation of in vitrotranslated product, proteins were synthesized by in vitro translation with rabbit reticulocyte lysate (RRL) in the presence of 35 S-labeled methionine and cysteine using EXPRE 35 S 35 S Protein Labeling Mix (PerkinElmer) (Fig. 2E and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Two recent studies using Neurospora and Synechococcus elongate reported that rare codons present in circadian genes play a critical role in maintaining the circadian rhythm (Xu et al 2013;Zhou et al 2013). In yeast cells, genes encoding membrane and secretory proteins are enriched with rare codons at positions critical for SRP recognition (Pechmann et al 2014). All these phenomena rely on rare codon-mediated translation slowdown that potentially influences co-translational folding (Yu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, non-optimal codons are postulated to slow down translation elongation. By tuning the elongation rate, codon usage bias has been reported to influence the behavior of nascent chains, including cotranslational folding as well as interaction with the signal recognition particle (SRP) (Pechmann et al 2014;Yu et al 2015).…”
Section: Introductionmentioning
confidence: 99%